Deficiency of the bZIP transcription factors Mafg and Mafk causes misexpression of genes in distinct pathways and results in lens embryonic developmental defects - Patel, Shaili D.; Anand, Deepti; Motohashi, Hozumi; Katsuoka, Fumiki; Yamamoto, Masayuki; Lachke, Salil A. (Frontiers in Cell and Developmental Biology, 2022)
Deficiency of the small Maf proteins Mafg and Mafk cause multiple defects, namely, progressive neuronal degeneration, cataract, thrombocytopenia and mid-gestational/perinatal lethality. Previous data shows Mafg-/-:Mafk+/- compound knockout (KO) mice exhibit cataracts age 4-months onward. Strikingly, Mafg-/-:Mafk-/- double KO mice develop lens defects significantly early in life, during embryogenesis, but the pathobiology of these defects is unknown, and is addressed here. At embryonic day (E)16.5, the epithelium of lens in Mafg-/-:Mafk-/- animals appears abnormally multilayered as demonstrated by E-cadherin and nuclear staining. Additionally, Mafg-/-:Mafk-/- lenses exhibit abnormal distribution of F-actin near the “fulcrum” region where epithelial cells undergo apical constriction prior to elongation and reorientation as early differentiating fiber cells. To identify the underlying molecular changes, we performed high-throughput RNA-sequencing of E16.5 Mafg-/-:Mafk-/- lenses and identified a cohort of differentially expressed genes that were further prioritized using stringent filtering criteria and validated by RT-qPCR. Several key factors associated with the cytoskeleton, cell cycle or extracellular matrix (e.g. Cdk1, Cdkn1c, Camsap1, Col3a1, Map3k12, Sipa1l1) were mis-expressed in Mafg-/-:Mafk-/- lenses. Further, the congenital cataract-linked extracellular matrix peroxidase Pxdn was significantly overexpressed in Mafg-/-:Mafk-/- lenses, which may cause abnormal cell morphology. These data also identified the ephrin signaling receptor Epha5 to be reduced in Mafg-/-:Mafk-/- lenses. This likely contributes to the Mafg-/-:Mafk-/- multilayered lens epithelium pathology, as loss of an ephrin ligand, Efna5 (ephrin-A5), causes similar lens defects. Together, these findings uncover a novel early function of Mafg and Mafk in lens development and identify their new downstream regulatory relationships with key cellular factors.